Pengaruh Profitabilitas, Struktur Modal dan Ukuran Perusahaan terhadap Nilai Perusahaan - Lia Dwi Lestari (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
The company's value reflects the market's assessment of the company's business prospects and ability to generate profits in the future. This value is often linked to the stock price and is the basis for investors to evaluate the company's performance. This study aims to determine the influence of profitability, capital structure, and company size on the value of companies in the food and beverage sector listed on the Indonesia Stock Exchange in the period 2019-2023. This study uses a quantitative method. There were 95 companies in the study population, and a sample of 24 companies was selected by the purposive sampling method. Data analysis was carried out by multiple linear regression using SPSS version 25. This study shows that profitability has a positive and significant influence on company value, while company capital structure and size have no effect on company value.